PENGELOLAN FASILITAS MUSEUM TUANKU IMAM BONJOL DI PASAMAN SUMATERA BARAT - Adilla kurnia Syadtari; Andi Moh Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Muesums are one of the tourist destinations when they want to travel. Good management of the facilities of a tourist attraction will be beneficial for the partu itself. Management of museum facilities in one of the factors supporting the information of a good and well-maintained museum. A good and well-maintained museum will provide a special attraction for visitors. That is why it is important to carry out a management by the manager. This reseach is a type of field research located at the Tuanku Imam Bonjol Museum, Pasaman Regency. The subjects in this study were 3 staff of the Tuanku Imam Bonjol Museum and 20 visitors to the Tuanku Imam Bonjol Museum with the object being the management of the Tuanku Imam Bonjol Musum’s facilities. The data were obtained using observation, questionnaires and interview and documentation techiques. The analytical method used is descriptive qualitative method, which produces desriptive data to describe a situation that was running at the time the research was conducted. Based on the result of the study, it can be seen that the Tuanku Imam Bonjol Museum is only managed by 3 staff who work concurrently. The obstacles in managing the museum are the lack of employess, and the lack of funds which causes many facilities not to be maintained properly. To overcome these obstacles, the goverment provides financial assistance has not been intensely implemented so that there are still many facilities of the Tuanku Imam Bonjol museum that are not maintained. Keywords: Management, Facilities, Museum. Constraints, Lack of funds, Lack of employees, Lack of facilities.